2021
DOI: 10.1111/pan.14158
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and safe removal of foreign bodies in the upper esophagus in children using an optimized Miller size 3 video laryngoscope blade

Abstract: Background Foreign bodies lodged in the upper esophagus in children may result in life‐threatening complications, especially with button batteries. Rapid removal is essential to prevent complications. Experts report that extraction with a suitable laryngoscope and a forceps is feasible under general anesthesia, but no further data had been available so far. Aims To study foreign body visualization and removal from the upper esophagus in children using a new optimized Miller size 3 blade video laryngoscope. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…If not visible on intubation, then video laryngoscopy should be considered as an adjunct in any situation where there is difficulty removing a foreign body from the proximal esophagus as we described above. Given the potential catastrophic nature of button battery ingestion, we echo Kaufman et al in suggesting that any institution with a pediatric anesthetist and the resources to intubate children should attempt to expediently remove the battery prior to attempts to transfer the patient to a more specialized institution [ 10 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…If not visible on intubation, then video laryngoscopy should be considered as an adjunct in any situation where there is difficulty removing a foreign body from the proximal esophagus as we described above. Given the potential catastrophic nature of button battery ingestion, we echo Kaufman et al in suggesting that any institution with a pediatric anesthetist and the resources to intubate children should attempt to expediently remove the battery prior to attempts to transfer the patient to a more specialized institution [ 10 ].…”
Section: Discussionmentioning
confidence: 91%
“…When examining the literature, case reports and observational studies of similar clinical scenarios were found in which laryngoscopy (direct or video) was a key component for foreign body removal in conjunction with a variety of instruments such as Magill forceps, hemostats, or alligator forceps [5][6][7][8][9][10]. Specifcally, Kaufman et al demonstrated that a Miller 3 video laryngoscope was successful in recovering foreign bodies from the proximal esophagus in all 22 patients in their observational study.…”
Section: Discussionmentioning
confidence: 99%
“…However, removal of foreign bodies from the esophagus with Magill forceps should be performed by experienced personnel because it may result in perforation (Bori Bata et al, 2021). Wide-angle view and good illumination of video laryngoscopes, providing better visualization and instrumentation compared with direct laryngoscopy, are advantageous in removing foreign bodies in the upper esophagus (Kaufmann et al, 2021). However, esophageal foreign bodies may not always be visualized with a videolaryngoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Published data suggest that VL might shorten duration of these surgical procedures, while minimizing adverse events occurence. Furthermore, VL has been successfully used to remove foreign bodies from hypopharynx, larynx and upper esophagus, both in adult and pediatric patients [33][34][35].…”
Section: Plos Onementioning
confidence: 99%